ANALISIS REGRESI MODERATING PRICE TO BOOK VALUE PERUSAHAAN YANG TERDAFTAR DI JII TAHUN 2014-2018 BERDASARKAN PROFITABILITAS DAN LEVERAGE DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI PEMODERASI - Ferdiana, Nikki; Widiawati, Hestin Sri (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
In a company, capital is important for the company's operating activities. For this reason, it is important for a company to attract investors to invest. The value of a company greatly influences the decision of potential investors to invest their capital. The purpose of this study was to analyze the effect of profitability and leverage on firm value with CSR as a moderating variable. In this research, firm value is proxied by Price to Book Value (PBV). In the population study selected were companies listed on the Jakarta Islamic Index (JII) in 2014-2018. The research sample was obtained using purposive sampling which was tested using Moderated Regression Analysis. Based on the results of hypothesis testing, it shows that partially Profitability (ROA) has a significant effect on Firm Value (PBV), with a significant t-test value of 0.031. Partially Leverage (DER) has a significant effect on Firm Value (PBV), with a significant t-test value of 0.012. CSR disclosure is not able to moderate the effect of Profitability on Firm Value (PBV), with a significant t-test value of 0.082. CSR disclosure is able to moderate the effect of Leverage on Firm Value (PBV), with a significant t-test value of 0.000. And simultaneously Profitability, Leverage, Profitability are moderated by CSR, and Leverage moderated by CSR has a significant effect on Firm Value (PBV), with a significant value of the f test of 0.000.